Shang-Chi and the quest for immortality - Ying, Victoria (Graphix, an imprint of Scholastic, 2023)
Sneaking out of the palace into the outside world to find the legendary Peaches of Immortality to gift to his father, 12-year-old Shang-Chi refuses to fail in his quest until he hears things that make him wonder if his father deserves to be saved.